ERROR ANALYSIS IN TRANSLATING ENGLISH FROM INDONESIAN OF SEMESTER SIXTH STUDENTS OF COKROAMINOTO PALOPO UNIVERSITY - Muhammad, Hasby; Magfirah, Thayyib (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2015)
This research is aimed to know the students errors in translating English from Indonesian from several text of the semester fifth students of Cokroaminoto Palopo University academic year of 2014/2015, some people considered translating is one of the most difficult skills in learning language, some people considered translating Indonesian to English even more difficult than translating English into Indonesian.The instrument consists of 17 texts as source language. Each text consists of several paragraphs which form a discourse. The paragraphs are from âBuku Dongeng Anti Korupsi Seri 1â. The translators are the undergraduate students of fifth semester of Cokroaminoto University. Data is located in the studentsâ English translation as target language. Data Â classified into 1) discourse errors, 2) syntactic errors, and 3) lexical errors. Syntactic errors will be classified into 1) sentence function, 2) tenses, 3) word order, 4) agreement rules, and 5) construction. Each sub-class is further sub-classified. Lexical errors are sub-classified into:Â  1) misselection of words, 2) derivational suffixes, and 3) function words.